Sunn hemp - An under-exploited versatile crop for soil nitrogen transformation and fibre production - Hariniharishma, V P; Subrahmaniyan, K; Elamathi, S; Arulmozhi, R; Manikandan, K; Sivasankari Devi, T; Abarajitha, P (Plant Science Today, 2025)
Sunn hemp (Crotalaria juncea L.) is a versatile legume belonging to the family Fabaceae, commonly used as a green manure or cover crop adding benefits to the cropping system. Nowadays, the excessive use of chemical sources of nitrogen to meet the crop demands has led to poor nitrogen use efficiency and significant environmental degradation. Reducing the use of synthetic fertilizers by supplementing them with green manure can minimize these negative impacts without compromising crop requirements. The incorporation of sunn hemp helps to improve the soil structure, water holding capacity, problem soil reclamation and increases nitrogen availability to the succeeding crop. Besides being used as a green manure crop, it is also grown as a fibre crop, due to the soft, strong and slightly lignified nature of its fibre. Synthetic fibres in blends are deleterious to the planet, requiring the search for natural and sustainable alternatives. The value of ecologically friendly resources has been increasing. Sunn hemp fibre is an underutilized lignocellulose fibre with a wide range of applications and an excellent substitute for synthetic fibres as it has natural characteristics such as high mechanical strength, low density, low cost, easy availability, biodegradability, etc. It is a fast-growing legume with high biomass, increased accumulation of nitrogen, weed suppressor, nematode controller and generates bioproducts viz., biofuel and bioenergy. The role of sunn hemp in nitrogen mineralization, their fibre properties and versatility in day-to-day activity make it a promising crop for the present and future generations. This review article presents the various uses of sunn hemp through past years of research.